Probabilistic load flowbased optimal placement and sizing of distributed generators - Hossain F.A.; Rokonuzzaman M.; Amin N.; Zhang J.; Mishu M.K.; Tan W.-S.; Islam M.R.; Roy R.B. (MDPI, 2023)
Electric load flow; Environmental impact; Genetic algorithms; Investments; Location; Operating costs; Probability distributions; Distributed generation; Distributed generation resources; Distributed generators; Distribution network; Electrical energy demand; Flow based; Location optimization; Optimal placement and sizings; Probabilistic load flow; Distributed power generation